Correlation Air CO Level with HbCo Level, Hemoglobin, and Blood Pressure to Street Vendors in The Gading Fajar Sidoarjo Street Vendor Area - Indira Ayuni Sri Pramasti; Ayu Puspitasari; Lully Hanni Endarini; Christ Kartika Rahayuningsih (Jurusan Teknik Elektromedik, POLTEKKES KEMENKES Surabaya, Indonesia, 2022)
Motor vehicles emit exhaust gas emissions that produce pollutants, one of the compounds contained is carbon monoxide (CO). CO may cause intoxication in humans if exposed for a long time especially street vendors because the work area is filled with vehicle fumes containing CO gas. High CO levels in the air indicate HbCO levels to increase. The increased of HbCO levels will cause abnormal hemoglobin levels and induce vasoconstriction which makes blood pressure increase. The purpose of this study was to prove the correlation between CO levels in the air with HbCO, hemoglobin, and blood pressure levels to street vendors in the Gading Fajar Sidoarjo Street Vendor Area. This research uses the Conway diffusion cell method and is an analytic observational study with a cross sectional design implemented at the Surabaya Health Laboratory Center and the Hematology Laboratory of Medical Laboratory Technology Department Poltekkes Kemenkes Surabaya in March 2022. Blood tests was carried out on 25 street vendors using random sampling technique. The results showed that average air CO level was 11.0 ppm and 13.3 ppm; mean HbCO levels 0.87%; mean hemoglobin levels 14.4 g/dL; mean systolic blood pressure levels 128 mmHg; and the mean of diastolic blood pressure levels 80 mmHg. The data were analyzed using SPSS. The outcome of normality test showed that the data was not normally distributed. Statistical tests was performed using Spearman correlation. The conclusion showed there was correlation between air CO level with HbCO level, hemoglobin level, and blood pressure level on street vendors in the Gading Fajar Sidoarjo Street Vendor Area. If CO levels in the air increase, then HbCO levels and blood pressure also increase. Street vendors are expected to always use Personal Protective Equipment (PPE) such as mouth masks when working to reduce the risk of exposure to CO gas and doing a healthy lifestyle as a preventive effort to avoid health problems.